Factors associated with postpartum depression among adolescents in Uganda - Atuhaire, Catherine; Cumber, Samuel Nambile (The Pan African Medical Journal, 2018)
Postpartum depression (PPD) is a common and disabling public health complication of the postpartum period in women. It is believed to occur three times more commonly in developing countries than in the developed world and is more prevalent among women in the first six weeks after birth. Research suggests that postpartum depression is more commonly diagnosed among adolescents and may be a risk factor for poor growth and development in children born to these mothers. Therefore, adolescents are a special age group that requires specific health care maternal interventions in order to detect and treat post-partum depression.
Keywords: Postpartum; Depression; Risk factors; Adolescents; Uganda